The Relationship Between Subdistrict Spatial Development, Agricultural Land Conversion Rate, and Business Investment Growth in Pacitan Regency - Maulana, Mohamad Rizki; Kurniawan, Edi; Nayan, Nasir Bin; Nugraha , Satya Budi (Universitas Lampung, 2025)
The regional development of Pacitan Regency is significantly influenced by land-use conversion dynamics and business investment activities based on the KKPR (Conformity of Spatial Utilization Activities), particularly following the construction of strategic infrastructure such as the South Coast Route (JLS). This study aims to analyze the relationship between regional development, the rate of agricultural land conversion, and the rate of KKPR-based investment across 12 subdistricts using a quantitative approach. Data were collected from infrastructure availability, land conversion requests, and KKPR permits, then analyzed using the scalogram method, centrality index, and multiple linear regression via SPSS. The results indicate that Pacitan Subdistrict functions as the primary service center with the highest score (455.59), also recording the highest land conversion rate. The correlation between regional development and land conversion is very strong, whereas the relationship with investment rate is statistically insignificant. Regression analysis shows land-use conversion as the dominant influencing factor (R² = 0.967). This study highlights the urgency of land conversion control and spatially equitable investment strategies to support sustainable and balanced regional development